The role of performance management in Achieving Organizational success - سلمان فاضل حمد; ابراهيم صفا محمد (Journal of Economics and Administrative Sciences, 2016)
The idea of this research is the basis of the role exercised by the dimensions of performance management (Performance Planning- performance evaluation- improve the performance and development- feedback - Review and Performance Monitor) In order to achieve the success Organizational Is through the (strategic vision- the operational activity- development of the company- selection of personnel- the company’s culture- Leadership and Management- Personal Development - Assessment and Review).And The research aims to identify the extent of the responsibility of performance management in achieving success Organizational through main hypotheses branched out by the sub-hypotheses to knowing out the between research and impact variables through the use of a number of statistical methods. And researcher used personal interviews and field homeliness and to questionnaire a tool for measuring and data on the sample in the collection of the practical side. And so to answer questions on the problem of research. And it may be distributed to the 66 members of their (Director- assistant Director) in the General Company of Cotton Industries Baghdad– Kadhimiya and have been relying on the program (spss) statistical and some statistical measures such as the arithmetic mean. standard deviation. The coefficient of variation, Simple deviation coefficient, Multi-deviation and coefficient as well as leveraged subjected to sincerity and stability to ensure the validity of statistical result have also been relying on researches and studies concerning the researches in the theoretical side. And in the light of the statistical results Find reach a number of conclusions was the most important of the impact of significant differences between the performance management and success Organizational in the General Company of Cotton Industries Baghdad–Kadhimiya addition to a set of recommendations by the researcher believes that it may contribute to addressing some of the problems and constraints faced by the company surveyed.